THE USE OF PRAAT IN LEARNING ENGLISH DEBATE IN INDONESIAN EFL CLASSROOM - Rahmatunisa, Wulan; Syarifudin, Syahrul (University of Kuningan, 2021)
This study aims to analyze the elements of suprasegmental sound in English debates consisting of stress and intonation by using the PRAAT computer program and students' perceptions toward the use of PRAAT in learning English debate. The data of this study were taken from the practice of debate in the General English class which is a compulsory course in Universitas Kuningan. A total of 30 students from one class of General English were involved in this study. The method used is a mixed method. Several instruments were used to collect data including observation and documentation for qualitative data, and questionnaires for quantitative data. PRAAT program version 6.0.33 was used to analyze the stress and intonation patterns, while questionnaire was used to determine students’ perceptions toward the use of PRAAT in mastering English debate. The results showed that the use of intonation and stress can affect the meaning of speech, especially in debate. Furthermore, students gave a positive response to the use of the PRAAT application in understanding the correct intonation patterns and pressure in speaking English.Keywords: PRAAT; debate; EFL classroom